Motivations of BS Hospitality Management Students at Ilocos Sur Polytechnic State College, Philippines - Cherie B. Orpia; Ivy Cacabelos (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
As the tourism and hospitality industries adapt to evolving local and global demand patterns around the world, employment at all skill levels is anticipated to rise, thus increased the demand for educated professionals. However, the COVID-19 pandemic had the impacted educational institutions and the tourism industry. Therefore, designing a curriculum involves a more profound knowledge of why students enroll in a course as they fill the positions assigned by the industry. Thus, the study sought to determine the perceptions of BS Hospitality Management students to provide significant inputs to the development of programs for the students in relation to their career opportunities. The study ascertained the relationship between the 159 respondents' profiles and their motivational elements using a descriptive approach. The survey's key findings indicated that the BSHM students at ISPSC were highly motivated to pursue their degree because they perceived the field attractive for employment; and the prospects for personal and work-related opportunities, though faced with uncertainties during the pandemic. The study discovered a correlation between gender and employment opportunities. It highlighted how gender differed in their motivation to pursue the course in terms of job opportunities. The study recommends that the institution should develop a college action plan for students’ making the transition from secondary to college to guide them in selecting the right courses. It should also develop the career manegemnt skills necessary for long term career success to prepare the students’ in addressing their career perceptions and uncertainties about their future profession in the tourism industry.